IMULASI PENCAMPURAN REAKTAN UNTUK PRODUKSI BIODIESEL PADA REAKTOR BERPENGADUK STATIK - Ni Putu Dian Nitamiwati, Armansyah Halomoan Tambunan, dan Lilik Pujiantoro Eko Nugroho (Jurnal Teknologi Industri Pertanian, 2018)
Application of static mixer is expected to enhance yield of biodiesel production and reduce catalyst requirement. Static mixer could increase the mixing effectiveness of oil and methanol, so that FAME yielded at the reactor would increase and could reach the desired level of conversion with lower catalyst requirement.A more in-depth study of the mixing and its relation to the effectiveness of transesterification reactions is indispensable to obtain important parameters which is necessary in process improvement and reactor design. The objective of this study was to examine the flow profile and its relation on mixing of oil and methanol in a continuous type reactor using computational fluid dynamics (CFD). Simulation was conducted using five scenarios of mass flow rate in the range of 5-20 L/min for oil and 0.6-2.4 L/min for methanol. It was observed that the static mixer elements can increase the uniformity of vorticity, which indicates that the flow is not only moved on the mainstream (axial direction) but also moves toward the y-axis and the z-axis randomly as well as rotational motion. The uniformity of vorticity along the static mixing reactor provided a better chance of mixing and increase the possibility of reactions between molecules of reactant. Keywords : biodiesel, transesterification, static mixer, computational fluid dynamics (CFD), vorticity